Research on outdoor special effect device for night forest park theme park - et.al, You-Suk Kim (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Recently, there have been many forest park theme parks for night tours. Various media technologies are installed in these forest park theme parks. A case study was conducted to find out the purpose and use of various media technologies used in forest park theme parks at night. We divided media technology into three major types of forest park theme parks currently in operation at home and abroad. The case was analyzed by dividing the media technology into forms that used special effects for stage performances, forms with interactive technology, and forms of lighting used for the atmosphere of the theme park. The analysis of the cases with three factors has resulted in the pros and cons of the cases in each part. The advantage is that special effects, interactive technology, and theme lighting are pioneering the media market by bringing out a new type of attraction called the Forest Park Theme Park. The first solution to this was to overcome the difficulties caused by outdoor installation in nature. It was a method to maintain temperature, humidity, dust, etc. in factors such as housing of electronic electrical equipment elements and covers of lighting. Second, we found elements that do not fit in nature. Most of the factors that were not aesthetic to the use of content were artificially installed. To compensate for this, elements such as electroplate ng tubes and camouflage control boxes should be applied from the content design and spatial design stages. By optimizing the essential elements for operation and harmonizing with nature, visitors can minimize visual fatigue and maximize aesthetics. The needs and complements of the design of the forest park theme park studied in this paper deal with the areas that need to be improved for users who have come to the night tour. This is meaningful for the development of a more enjoyable and pleasant forest park theme park.